Optimizing the removal of nitrate by adsorption onto activated carbon using response surface methodology based on the central composite design. Issue 1 (2nd January 2020) - Taoufik, Nawal; Elmchaouri, Abdellah; Korili, Sophia A.; Gil, Antonio
Abstract : This study sheds light on the adsorption process for the removal of nitrate ions from synthetic aqueous solutions. This contaminant pose a potential risk to the environment and can cause health effects including cancers and methemoglobinemia in infants. When the adsorption process is carried out, the effect by the several operating parameters such as initial nitrate concentration, pH, mass of activated carbon, and contact time becomes apparent. The essential process variables are optimized using response surface methodology (RSM) based on the central composite design (CCD) experiments. For this purpose 31 experimental results are required to determine the optimum conditions. The optimum conditions for the removal of nitrates is found to be: initial nitrate concentration = 15 mg/L; initial pH 4.0; mass of activated carbon = 25 mg, and contact time = 70 min. At these optimized conditions, the maximum removal of nitrates is found to be 96.59%.